Action Of Naloxone And Acetorphan, On Uterine Contractions Induced By Oxytocin -in Periparturient Rat In Vivo - Ounassa Adjroud (Synthèse, 1997)
Theffects' in vivo of acetorphan, an _enkephalinase inhibitor and naloxone, an opiate antagonist on the - - oxytocin- induced myometrial mechanical activity were studied at day 21 of pregnancy in rats. Acetarpban" I 10 mg kg -1 (i.v.) increased (344%) spontaneous uterine contractions duration only at 0-10 min period, but - did not modify amplitude. This increase in the duration was blocked by naloxone 5 mg ks -1, which had no effect on the amplitude or duration of contractions when given alone. Oxytocin (~T), I, 10 and I 100 mIU (i.v.) stimulated in a dose dependent manner, spontaneous uterine contractions duration but did not alter the amplitude of contractions. Blocking the opioid peptides by naloxone, 5 mg kg -1 (s.c.) injected --10min before OT strongly potentiated the effect of the lowest dose of OT (1 mlU) b-yabout of 59&Ofn and doubled the amplitude of contractions during the 30 min observation period. When acetorphan, 10 mg kg _-1 (i.v.) administered 30 min before the lowest dose of OT studied, 1 mID (i.v.), It induced a slight increase by .about 88% in uterine contractions duration produced by OT alone, The amplitude remained unchanged. These -results suggested that uterine contractions induced by OT in late pregnancy in rats might be regulated by enkephalinergie and enkephalinasic systems